2013
DOI: 10.1084/jem.20121611
|View full text |Cite
|
Sign up to set email alerts
|

Tob1 plays a critical role in the activation of encephalitogenic T cells in CNS autoimmunity

Abstract: Loss of antiproliferative gene TOB1 results in more severe EAE driven by augmented pathogenic T cell responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 30 publications
4
46
0
Order By: Relevance
“…Mononuclear cells (MNCs) were isolated from the spleens of Tob1 −/− mice and Tob1 +/+ littermates at baseline and at day 15 after EAE induction (15 dpi), corresponding to the peak of the disease11. Total RNA was purified from each cell sample and subjected to microarray hybridization as described in the Material and Methods section.…”
Section: Resultsmentioning
confidence: 99%
“…Mononuclear cells (MNCs) were isolated from the spleens of Tob1 −/− mice and Tob1 +/+ littermates at baseline and at day 15 after EAE induction (15 dpi), corresponding to the peak of the disease11. Total RNA was purified from each cell sample and subjected to microarray hybridization as described in the Material and Methods section.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, IL4I1 has been shown to maintain the expression of Tob1, an antiproliferative protein, which is necessary to limit CD4 + T cell proliferation (Santarlasci et al , 2014). Furthermore, Tob1 deficiency in mice with EAE results in enhanced CNS inflammation (Schulze-Topphoff et al , 2013). In fact, individuals presenting with an initial demyelination episode who also display low Tob1 expression are more likely to progress to multiple sclerosis from clinically isolated syndrome than those with high Tob1 level (Corvol et al , 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, by investigating the role of Tob1 in EAE, it was found that immunization of Tob1 −/− mice with myelin oligodendrocyte glycoprotein peptide 35-55 resulted in an earlier disease onset, an increase in the maximum clinical score, and a greater and sustained disease severity in comparison with wildtype mice [23]. The exacerbated EAE phenotype in Tob1 −/− mice associated with augmented CNS inflammation, increased infiltration of CD4 + and CD8 + T cells, and higher numbers of myelinreactive Th1 and Th17 cells, whereas the numbers of regulatory T cells were reduced [23]. Thus, our data provide an explanation for the reason why Tob1 can play an important regulatory role in the development and/or severity of this important disorder of the CNS and perhaps of other Th17-related chronic inflammatory processes in both humans and mice.…”
Section: High Tob1 Expression In Th17 Cells Is Dependent Upon Il4i1 Umentioning
confidence: 99%